A case of acute pulmonary embolism with severe haemoptysis. Issue 208 (December 2021) - Le Mao, Raphael; Tromeur, Cécile; Couturaud, Francis
Abstract: Haemoptysis is a potentially life-threatening symptom, which require immediate management. Haemoptysis is a challenging situation because the potential numerous causes lead to strongly different therapeutic options (medical, surgical, systematic embolization). When haemoptysis occurred at the acute phase of pulmonary embolism, anticoagulation should be stopped and inferior vena cava filter is justified. Based on a case report of massive haemoptysis related to pulmonary infarction (i.e., no other causes) in a patient with a unprovoked intermediate high-risk pulmonary embolism, we describe the dilemma set in the paradox between the need for stopping anticoagulation and the need to treat the cause of haemoptysis which is also anticoagulation. If anticoagulation should be stopped, however, the optimal management regarding the use of specific reversal agents or prothrombotic plasma concentrates remains uncertain and weakly documented. After haemoptysis has been resolved, there is also uncertainty on restarting anticoagulation modalities. Regarding long-term management, the decision to stop at three months or to prolong indefinitely based on international recommendation is also challenging in the case of unprovoked severe pulmonary embolism. In this particularly high risk situation, multidisciplinary expertise is essential. Highlights: Massive haemoptysis, related to pulmonary infarction during acute phase pulmonary embolism, is challenging. Anticoagulation should be stopped and inferior vena cava filter is justified. After haemoptysis has been resolved, there is also uncertainty on restarting anticoagulation modalities. Regarding long-term management, the decision to stop at three months or to prolong indefinitely is also challenging. In this particularly high-risk situation, multidisciplinary expertise is essential.